Implementing dynamic power feed-in limitations of photovoltaic systems in distribution grids for generation expansion planning - Alexander Konrad; Robert Gaugl; Christoph Maier; Sonja Wogrin (Energy Strategy Reviews)
The rapid growth of photovoltaic (PV) systems in Austria’s medium- and low-voltage grids has intensified challenges in grid access, with technical limits increasingly leading to restrictions on full feed-in power. This issue has sparked discussions about limiting PV feed-in power and the implications for both generated and curtailed PV energy. At the same time, expanding PV capacity remains critical to achieving future climate targets. However, there is a lack of robust methodologies to quantify the impact of PV feed-in limitations when implemented in an optimization model. This impact affects both the curtailed energy and the increase in maximum PV installation capacity and total energy production. To address this gap, we have developed a mathematical formulation of dynamic PV feed-in limitations and integrated it into an optimization model. This approach enables a comprehensive evaluation of its effects on PV integration potential and energy curtailment, validated through case studies on four representative real-world Austrian medium- and low-voltage grids. We analyzed maximum PV expansion, energy generation, and curtailment under feed-in constraints. The results highlight the potential for integrating up to 32% additional PV systems within existing infrastructure while keeping PV curtailment relatively low, i.e. at 2%. We provide actionable insights for grid operators and policymakers aiming to balance renewable energy expansion with grid reliability.